Elucidating the photoprotection mechanism of eumelanin monomers - Ghosh, Paulami; Ghosha, Debashree (Journal of Physical Chemistry B, 2017)
Eumelanin, the functional polymer in human skin, forms a heterogeneous layered structure intrinsic to its broadband monotonic spectra. The inherent structural heterogeneity of eumelanin makes the photoprocesses very complex and diverse in nature. Due to this diversity, a complete mechanistic picture of these photoprocesses, essential to understanding the photoprotective properties, has been missing to date. In this study, we recreate the potential energy surfaces of the low-lying excited states of the multiple monomeric forms of eumelanin constituents that play a prominent role in either photoprotection or photodamage pathways. Our results indicate a diverse set of pathways for the photoexcited species to relax back to the ground state, that depends on the specific monomeric form. Furthermore, the excited state reaction channels show the scope of extensive interconversion between the different monomers and therefore, we propose that the heterogeneity of eumelanin is key to its photoprotection capability.